Analisis Putusan Hakim Pengadilan Agama Dalam Perkara Izin Poligami - Fauzi Rahmat Pamula; Sayehu; Usman (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
Permission to practice polygamy can only be granted by the Religious Court if a husband has fulfilled the alternative requirements in accordance with Article 4 paragraph 2 and fulfilled the cumulative requirements of Article 5 paragraph 1 of the Law. No. 1 of 1974. However, in the decision of the Serang Religious Court, decision no. 0602/Pdt.G/2020/PA.Srg., alternative conditions not met; Nevertheless, the judge still granted the polygamy permit. By paying attention to the formulation of the problem that has been mentioned, the aim of this research is to find out the analysis of the judge's considerations in this polygamy permit application case. In this research using normative juridical methods, it was concluded that the judge's consideration in granting permission for polygamy was based on considerations of benefit, namely to avoid adultery, obtain consent from the first wife, and fulfill procedural requirements in the form of written evidence and two witnesses. Even though the alternative conditions are not met in accordance with Article 4 paragraph 2 of Law no. 1 of 1974, but based on maslahah considerations, polygamy is considered an urgent alternative, on the other hand, husbands can be fair to their wives, both from a material and biological perspective.   Keywords: polygamy permit, judge, religious court